PENYALUTAN KACANG RENDAH LEMAK MENGGUNAKAN SELULOSA ETER DENGAN PENCELUPAN UNTUK MENGURANGI PENYERAPAN MINYAK SELAMA PENGGORENGAN DAN MENINGKATKAN STABILITAS OKSIDATIF SELAMA PENYIMPANAN [Ether Cellulose Coatings by Dipping on Partially Defatted Peanuts - Made Darawati; Yudi Pranoto (Jurnal Teknologi dan Industri Pangan, 2010)
This research aimed to reduce oil uptake during frying and to improve the oxidative stability of a partially defatted peanuts (PDP) product by coating with ether cellulose-based substances, namely carboxymethyl cellulose (CMC), hydroxyprophyl methyl cellulose (HPMC), methyl cellulose (MC) and hydroxyprophyl cellulose by dipping method. The research was conducted through following steps: preparation of ether cellulose-based edible film and evaluation of the properties, coating application on PDP before frying, and measurement of the oil content, water content, hardness, and then determination of the best dipping method, evaluation of edible coating on PDP with selected dipping method and measurement of colour, peroxide value, and TBA value of fried coated products, and study on oxidative stability of fried coated-PDP during 14 days of storage. Results showed that ether cellulose based-edible film had 0.042-0.052 mm thickness, tensile strength of 7.93-23.04 MPa, elongation of 6.81-29.10%, water vapor transmission rate of 13.18-16.65g/m2.h. and oxygen permeability of 4.57-6.24x10-9 g/m.d.Pa. Ether cellulose-based coatings had significant effect on oil content and water content of PDP (p<0.05).  CMC-based edible coatings before frying reduced oil content as much as 21.27% on PDP.  Ether cellulose-based edible coatings improved oxidative stability on PDP during 14 days of storage.  Edible coatings with CMC before frying had the lowest increase in peroxide value and TBA value.